σ-Bonded organochromium(III) complexes. 3. decomposition in acid solution of chromium(III) complexes containing pyridylmethyl and polydentate amine ligands - Crouse, Karen; Goh, Lai-Yoong (ACS Publications, 1986)
The decomposition of σ-bonded (pyridylmethyl)chromium complexes, 2- and 3-NC5H4CH2CrLn(L = dap (1,3-diaminopropane), dien (diethylenetriamine), trien (triethylenetetramine), and [15]aneN4(tetraazacyclopentadecane)), was investigated in aqueous perchloric acid under aerobic conditions. Except for L = 15[ane]N4, Cr-C bond scission was preceded by complete aquation in the case of the 2-isomers and partial aquation for the 3-isomers. The aquation rates were compared with those of inorganic chromium complexes containing similar amine ligands. Kinetic data for the Cr-C bond cleavage were correlated with those for the analogous ethylenediamine (en) and aquo (H20) systems. The activation parameters and product studies are in support of a homolytic pathway for the Cr-C bond cleavage.